Development of Socioscientific Issues-Based Teaching Materials to Improve Learning Outcomes and Students’ Environment Awareness on The Environmental Changing Material - Ma'rufah, Dian Muhimmatun; Ngabekti, Sri; Setiati, Ning (Journal of Innovative Science Education, 2021)
Environmental problems can’t be avoided in big cities including Semarang city. This needs to be raised in learning one of them through the development of teaching materials based on socioscientific issues. The purpose of this study is to develop teaching materials based on socioscientific issues, test the effectiveness of teaching materials, analyze students and teacher responses of teaching materials. This research is a Research & Development. We develop teaching materials based on socioscientific issues by utilizing local realities of Environmental Change in Semarang city. The expert’s validation of material and media was 87.04% and 97.92%. It was categorized in very valid criteria. Teaching materials developed were effective in increasing students' cognitive learning outcomes with classical completeness by 86.36% and n-gain test by 0.55. Students’ environmental care attitudes increase with a percentage of 83.33% in very caring criteria. The readability response of students and teachers was 83.75% and 97.69% in very good criteria. The practicality responses of students and teachers was 86.25% and 95% with very practical criteria. The conclusion of this study is teaching material developed are effective for improving cognitive learning outcomes and students’ environmental care attitudes. The response of students and teachers in readability is very good, the response of students and teachers in practicality is very practical.